2021
DOI: 10.3389/fnhum.2021.616591
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal Mapping of the Face Selective Ventral Temporal Cortex–A Group Study With Clinical Implications for ECS, ECoG, and fMRI

Abstract: Face recognition is impaired in patients with prosopagnosia, which may occur as a side effect of neurosurgical procedures. Face selective regions on the ventral temporal cortex have been localized with electrical cortical stimulation (ECS), electrocorticography (ECoG), and functional magnetic resonance imagining (fMRI). This is the first group study using within-patient comparisons to validate face selective regions mapping, utilizing the aforementioned modalities. Five patients underwent surgical treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 87 publications
2
16
0
Order By: Relevance
“…Stimulating the posterior face-selective regions with SEEG (IOG and LatMidFG) often evoked perceptual changes (facial elements in disarray, seeing the different faces as being the same, facial palinopsia, Table 1). This observation is in agreement with ECOG DES studies consistently reporting facial perceptual changes (usually a perceptual distortion) when stimulating the right LatMidFG (Parvizi et al, 2012;Rangaranjan et al, 2014;Schalk et al, 2017;Schrouff et al, 2020;Sanada et al, 2021; see also Mundel et al, 2003). In contrast, as noted above, DES inside the right AntFG did not evoke perceptual effects (case 3, CD, Table 1).…”
Section: Functional Differences and Similarities Of The 3 Key Regions For Firsupporting
confidence: 90%
See 4 more Smart Citations
“…Stimulating the posterior face-selective regions with SEEG (IOG and LatMidFG) often evoked perceptual changes (facial elements in disarray, seeing the different faces as being the same, facial palinopsia, Table 1). This observation is in agreement with ECOG DES studies consistently reporting facial perceptual changes (usually a perceptual distortion) when stimulating the right LatMidFG (Parvizi et al, 2012;Rangaranjan et al, 2014;Schalk et al, 2017;Schrouff et al, 2020;Sanada et al, 2021; see also Mundel et al, 2003). In contrast, as noted above, DES inside the right AntFG did not evoke perceptual effects (case 3, CD, Table 1).…”
Section: Functional Differences and Similarities Of The 3 Key Regions For Firsupporting
confidence: 90%
“…First, with the exception of early studies (Allison et al, 1994 andPuce et al, 1999) and the case reported by Parvizi et al, (2012) who was not impaired at naming famous face pictures, ECOG DES studies with face stimuli essentially required subjects to passively look at faces (Mundel et al, 2003;Rangarajan et al, 2014;Rangarajan & Parvizi, 2016;Sanada et al, 2021;Schalk et al, 2017;Schrouff et al, 2020) or to perform face detection tasks (Chong et al, 2013;Keller et al, 2017), without specifically testing for FIR impairment.…”
Section: A Seeg Advantage In Evoking Fir Impairments?mentioning
confidence: 99%
See 3 more Smart Citations